A systematic review of cardiovascular risk management interventions among community-dwelling people with chronic disease - Henriques, Helga Rafael; Pinto, Joana; Faria, José; Augusto (Millenium - Journal of Education, Technologies, and Health, 2021)
Introduction: Cardiovascular diseases (CVD) represent the main cause of mortality in the world. Arterial hypertension, obesity, diabetes, dyslipidemia, sedentary lifestyle and smoking are risk factors for CVD and the main chronic diseases. The evidence on the effectiveness of interventions to promote cardiovascular risk management in chronic disease is still laconic. Objective: To identify the components of cardiovascular risk management programs for people with chronic illness in the community, as well as the behavioral change techniques used. Methods: A systematic literature review was carried out in November 2020, following the recommendations of PRISMA. We used the MEDLINE, CINAHL, SCOPUS, Web of Science, Cochrane, Academic Search Complete and Mediclatina databases. The bibliographic sample consisted of 21 articles, involving 26040 people with chronic disease. Results: The intervention programs are heterogeneous, concerning their components, knowledge disciplines involved, duration and strategies used. The most frequently used behavioral change techniques are advice and negotiation. Conclusion: We can conclude that educational interventions are a consensual approach to the management of CVD risk in people with chronic diseases. The heterogeneity of the interventions doesn’t allow us to determine the program's effectiveness. Further research is needed to make the results more consistent.